PROBLEMS OF THE MODERNIZATION OF THE ECONOMY OF BULGARIA: PROBLEMS OF THE MODERNIZATION OF THE ECONOMY OF BULGARIA - Totev , Hristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Innovation and modernization of the economy "We do not like the traditions -Henry Ford said - we want to live now and the only history that means something - this is what we are doing at that moment." For the creator of one of the largest markets in the world, man and businessman who lived in the time of the birth of the " American miracle " was easily and naturally to ignore the history. Today there are no such individuals nor in America or the world. In many countries facing the dilemma of restructuring the economy , debate on economic policy lead to the question , how to build a competitive economic structure , i.e. how structural adjustment to be bound to external economic exchange in order to form comparative advantages.